Art. 102 AEUV und die Rolle der Ökonomie Eine Weiterentwicklung des more economic approach - Rohner, Tristan (Europäisches Wirtschaftsrecht, 2023)
How can economic insights be better used in the interpretation and concretization of the prohibition of abuse under Article 102 TFEU? The author answers this research question and comes to the conclusion that the more economic approach to Article 102 TFEU has failed. To prove this, he utilizes the method of qualitative content analysis from social science for the legal analysis of decisions. Subsequently, the author shows that economic insights can be decisive not only for the content of the prohibition of abuse under Article 102 TFEU, but also for the process of interpretation and concretization. He develops a method to translate economic insights into legal rules.